2017
DOI: 10.1017/s0007485317000177
|View full text |Cite|
|
Sign up to set email alerts
|

Real-time PCR assay for distinguishingFrankliniella occidentalisandThrips palmiArnika Przybylska, Żaneta Fiedler, Aleksandra Obrępalska-Stęplowska

Abstract: Thrips palmi and Frankliniella occidentalis (order Thysanoptera) are thrips species that represent major plant pests. They are polyphagous insects capable of adversely affecting crop production. As such, in the European Union, these thrips species should be regulated as quarantine organisms. T. palmi and F. occidentalis can cause considerable damage to susceptible plants by feeding on them and transmitting several viruses responsible for serious plant diseases. Successful pest control strategies are based on a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 37 publications
(47 reference statements)
0
9
0
Order By: Relevance
“…The RPA assay reported here was sensitive enough to amplify as little as 0.2 ag of template DNA, 10 9 -fold more sensitive than PCR using the same primers. The previously reported sensitivity of real-time PCR for discrimination of T. palmi was 1 pg (Przybylska et al 2017 ). The detection threshold for LAMP assay was 2 × 10 –10 parts of an adult T. palmi (Przybylska et al 2015 ), whereas the RPA assay could detect as low as 2.9 × 10 −13 parts of an adult considering 700 ng total DNA extracted from a single adult T. palmi .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The RPA assay reported here was sensitive enough to amplify as little as 0.2 ag of template DNA, 10 9 -fold more sensitive than PCR using the same primers. The previously reported sensitivity of real-time PCR for discrimination of T. palmi was 1 pg (Przybylska et al 2017 ). The detection threshold for LAMP assay was 2 × 10 –10 parts of an adult T. palmi (Przybylska et al 2015 ), whereas the RPA assay could detect as low as 2.9 × 10 −13 parts of an adult considering 700 ng total DNA extracted from a single adult T. palmi .…”
Section: Discussionmentioning
confidence: 97%
“…No change in color with DNA of thrips collected from chilli, onion, tomato, and grape plants confirmed that different thrips species were present between the small-subunit ribosomal RNA (rRNA) and large-subunit rRNA genes. This hypervariable region has been preferred by several workers for discrimination of thrips at the species level because of a larger interspecific genetic distance than mtCoI (Glover et al 2010;Przybylska et al 2015Przybylska et al , 2017Ghosh et al 2020). Recent reports of several variants of mtCoI in T. palmi (Iftikhar et al 2016;Tyagi et al 2017;Ghosh et al 2020) were another reason to choose ITS2 over mtCoI in designing the RPA primers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphometric key-based identification of thrips species is timetaking, labor-intensive, requires expertise, and dependent on developmental stage as only adults can be identified. The speed, reproducibility, and accuracy of molecular techniques have made them a valuable tool for identification of thrips vectors [13,[29][30][31][32][33][34][35][36]. The simultaneous identification of several species using multiplex PCR has become popular for its added advantages of saving time, money, and effort over other methods of diagnosis [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of this qPCR is 95%, and the sensitivity is 0.1 pg µL −1 . Przybylska and colleagues [ 184 ] have developed a duplex qPCR based on the 5.8S ITS2 ribosomal region to discriminate between T. palmi and F. occidentalis . This sensitive assay can detect 1 pg of template DNA.…”
Section: Pcr-based Identification Of Thrips Using Molecular Markersmentioning
confidence: 99%